World of Echo : Noise and Knowing in Late Medieval England - Lears, Adin E. (Adin Esther), 1982- (Book collections on Project MUSE., 2020)
"By showing how medieval thinkers used the idea of noise to conceive of lay experience and expression, this book amplifies the history of cultural and social hierarchies around aesthetic experience and gives voice to alternate ways of knowing"--